How Students from Dysfunctional Families Build Academic Resilience and What Helps Them along the Way: A Systematic Review - Andi Nadia Qarirah Rafifah Alisyahbana; Haerani Nur; Muhammad Daud (ITScience (Information Technology and Science), 2025)
The increasing prevalence of dysfunctional families poses challenges to students' academic performance. However, some students display academic resilience, maintaining achievement despite adversity. While most studies focus on Western contexts, this research explores how academic resilience is manifested and supported by protective factors within an Asian cultural context, where values may shape resilience differently. This systematic review followed PRISMA guidelines, examining eight peer-reviewed studies (2015-2024) across six Asian countries. Studies were identified through comprehensive database searches (Google Scholar, PsycINFO, Scopus, PubMed), selected based on rigorous inclusion criteria, and analyzed using structured narrative synthesis due to methodological heterogeneity. Academic resilience is manifested through sustained academic performance, learning motivation, emotional regulation, and independent decision-making despite family adversity. Protective factors operated at multiple levels: individual (self-efficacy, intrinsic motivation), familial (supportive relationships, authoritative parenting), educational (teacher support, school attachment), and sociocultural (collectivist values emphasizing education). These factors functioned interdependently, creating dynamic resilience systems shaped distinctively by Asian cultural contexts. Academic resilience in students from dysfunctional families, mainly in Asia, emerges through synergistic interactions between internal resources and external supports, and is profoundly shaped by Asian cultural values framing education as a familial duty. Educational institutions serve as critical resilience-fostering environments, underscoring the need for culturally-responsive interventions across ecological domains.